Construction and application case study of a “Primary Care-focused” county health system development index - Ziqi Li; Ping He; Beibei Yuan; Wei Zhang; Hanyi Xu; Qianchen Wei; Qingyue Meng; Jin Xu (Chinese General Practice Journal)
Background: “Focusing on primary care” is the primary principle guiding health system in China. However, there is a lack of effective measurement tools in practice. Objective: The study sought to construct an index of ''primary care-focused'' county health system development index and perform empirical case analysis with two counties. Methods: The study was conducted from 2021 to 2022. The index (including its sub-indicators, scoring methods and weights) was constructed based on a literature review and experts’ consensus (via a Delphi technique). Then, it was applied in 2 counties in Guangxi Zhuang Autonomous Region, based on data collected from a range of sources from 2020 to 2022, including surveys for community residents, patients and health professionals survey, institutional survey, medical insurance claims data, as well as data of key informant interviews. Results: The results of Delphi method showed that the authority coefficient of experts was 0.91, the coefficients of variation of two rounds of consultation were 0.14 and 0.13, respectively. The constructed index system contains 3 domains, 15 dimensions, and 36 indicators, with a comprehensive index calculation method. The results showed that the overall scores for the two counties in Guangxi Zhuang Autonomous Region were 58.62 and 52.57, respectively. The scores of both counties were below the current national benchmark (60.00 points). Conclusion: Within the constraint of data availability, the index system constructed in this study could be applied to monitor and evaluate the extent that county health systems have achieved “primary care focus”. Its application may improve visibility and priority of primary care development, facilitate the development and implementation policies to strengthen primary care.